Perivascular adipose tissue contains functional catecholamines - Ayala-Lopez, Nadia (Blackwell Publishing Ltd, 2014)
The sympathetic nervous system and its neurotransmitter effectors are undeniably important to blood pressure control. We made the novel discovery that perivascular adipose tissue (PVAT) contains significant concentrations of catecholamines. We hypothesized that PVAT contains sufficient releasable catecholamines to affect vascular function. High-pressure liquid chromatography, isometric contractility, immunohistochemistry, whole animal approaches, and pharmacology were used to test this hypothesis. In normal rat thoracic aorta and superior mesenteric artery, the indirect sympathomimetic tyramine caused a concentration-dependent contraction that was dependent on the presence of PVAT. Tyramine stimulated release of norepinephrine (NA), dopamine (DA) and the tryptamine serotonin (5-hydroxytryptamine [5-HT]) from PVAT isolated from both arteries. In both arteries, tyramine-induced concentration-dependent contraction was rightward-shifted and reduced by the noradrenaline transporter inhibitor nisoxetine (1 μmol/L), the vesicular monoamine transporter inhibitor tetrabenazine (10 μmol/L), and abolished by the α adrenoreceptor antagonist prazosin (100 nmol/L). Inhibitors of the DA and 5-HT transporter did not alter tyramine-induced, PVAT-dependent contraction. Removal of the celiac ganglion as a neuronal source of catecholamines for superior mesenteric artery PVAT did not significantly reduce the maximum or shift the concentration-dependent contraction to tyramine. Electrical field stimulation of the isolated aorta was not affected by the presence of PVAT. These data suggest that PVAT components that are independent of sympathetic nerves can release NA in a tyramine-sensitive manner to result in arterial contraction. Because PVAT is intimately apposed to the artery, this raises the possibility of local control of arterial function by PVAT catecholamines.